Critical success factors of lean implementation in Vietnam manufacturing enterprises - Minh, Nguyen Dat (Journal of Production Engineering, 2018)
Lean Manufacturing (LM) is one of the systematic approach to achieve productivity improvement for organizations. LM focuses on the wastes elimination and non-value added activities from the production. Although many enterprises succeeded in applying LM around the world, there are only less than 20 per cent of them have achieved and maintained LM activities for the time. The aim of this research is to present the critical factors constituting the successful implementation of LM in Vietnamese manufacturing enterprises. There are nine are classified as the critical for the successful adoption of LM in Vietnamese enterprises.